Internal energy analysis with nanofluids in header and riser tube of flat plate solar collector by CFD modelling - Farhana, K.; Mahamude, A. S. F.; K., Kadirgama; M. M., Rahman; M. M., Noor; D., Ramasamy (IOP Publishing, 2019)
In this study, Computational Fluid Dynamics (CFD) modelling of internal energy with different nanofluids (TiO2 and crystal nano cellulose) studied. The modelling was three dimensional under Viscous Laminar model. The base fluid for nanoparticles was 60% water+40% ethylene glycol along with individual water and ethylene glycol fluids. Volume fraction of nanofluids was 0.5% and single-phase model used. The diameter of inlet and outlet was fixed of individual model and three kinds of designing model used here. The diameter of both header and riser tubes varied whereas the number of tubes varied only for riser. The results revealed that diameter and number of tubes (riser) do not affect on the internal energy. Since internal energy only depends on different properties of the inside fluids.